ggVennDiagram: An Intuitive, Easy-to-Use, and Highly Customizable R Package to Generate Venn Diagram - Gao, Chun-Hui; Yu, Guangchuang; Cai, Peng (Frontiers in Genetics, 2021)
Venn diagrams are widely-used diagrams to show the set relationships in biomedical studies. In this study, we developed ggVennDiagram, an R package that could generate automatically high-qualityVenn diagrams with 2-7 sets. The ggVennDiagram is built based on ggplot2, and it integrates the advantages of existing packages such as venn, RVenn, VennDiagram, and sf. Satisfactory results can be obtained with minimal configurations. Furthermore, we designed comprehensive objects to store the entire data of Venn diagram, which allowed free access to both intersection values and Venn plot sub-elements such as set label/edge and region label/filling. Therefore, high customization of every Venn plot sub-element can be fulfilled without increasing the cost of learning when user is familiar with ggplot2 methods. To date, ggVennDiagram has been cited in more than ten publications, and its source code repository has been starred by more than 140 GitHub users, suggesting a great potential in applications. The package is an open-source software released under the GPL-3 license, and it is freely available through CRAN (https://cran.r-project.org/package=ggVennDiagram).